Restrições ao uso de sistemas de medição de desempenho em pequenas e médias empresas: estudo de campo em indústrias de transformação do setor metal-mecânico - Gloria, Marcelo Guimarães (2014)
The Performance Measurement System (PMS) are one of the essential tools to withstand the demands of information at all levels within an organization, and also is an important means of measuring the effectiveness of their business strategy. However, due to several peculiarities present in Small and Medium Enterprises (SME), this tool is not always implemented and used in full. Given the above, this work aims to identify constraints that make it difficult the implementation and use of a PMS in SMEs. For this, a literature search and also a survey research was conducted, covering a unit of analysis of 21 industries in the metal-mechanical sector. This research was conducted in the region of Limeira, an important industrial center, located within the São Paulo state. As a result, it was found that SMEs face many difficulties in implementing PMS and this phenomenon is due to the fact that SMEs have characteristics that differ from large companies. Factors such as lack of resources, excessive informality, lack of a strategic long-term vision and lack of knowledge of this tool have been identified as existing in most of the surveyed companies. These factors added the characteristics of business, become serious constraints to the development and use of this tool.